KONSELING TANDA BAHAYA KEHAMILAN - Sarina Ali (Adiba Aisha Amira, 2022)
Pregnancy is a series of processes that begin with conception or the meeting between an ovum and a healthy sperm followed by fertilization, nidation, and implantation. Normal women who are pregnant have a greater risk during their pregnancy. This is certainly a problem that requires the involvement of midwives as service providers to mothers and the community in the form of counseling on counseling about the danger signs of pregnancy, most maternal deaths occur during pregnancy, because it is very important to guide mothers and their families to recognize the danger signs that indicate that she needs to seek medical help immediately.